Mediated Contracts and Mechanism Design - Roland Strausz (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2010)
This note relates the mechanisms that are based on mediated contracts of Rahman and Obara (2010) to the mechanisms of Myerson (1982). It shows that the mechanisms in Myerson (1982) are more general in that they encompass the mechanisms based on mediated contracts. It establishes an equivalence between the two classes if mediated contracts are allowed to be stochastic.
urn:nbn:de:bvb:19-epub-13232-8
Keywords: 330; mediatedcontract; mechanismdesign; revelationprinciple; moralhazard; Vertragstheorie; Mechanismus-Design-Theorie; Mediation; Offenbarte Präferenzen; Moral Hazard; Theorie